What? Where? When? Why?
XVII, 319 p.
Keywords: Only in fairly recent years has History and Philosophy of Science been recog nised - though not always under that name - as a distinct field of scholarly endeavour. Previously, in the Australasian region as elsewhere, those few individuals working within this broad area of inquiry found their base, both intellectually and socially, where they could. In fact, the institutionalisation of History and Philosophy of Science began comparatively early in Australia. An initial lecturing appointment was made at the University of Melbourne immediately after the Second World War, in 1946, and other appointments followed as the subject underwent an expansion during the 1950s and '60s similar to that which took place in other parts of the world. Today there are major Departments at the University of Melbourne, the University of New South Wales and the University of Wollongong, and smaller groups active in many other parts of Australia, and in New Zealand.